2001
DOI: 10.1046/j.1365-3059.2001.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of European stone fruit yellows (ESFY or 16SrX‐B) phytoplasmas in apricots in Austria

Abstract: A severe decline of apricot trees, present in Austria for several years, has recently reached notifiable levels. Initial symptoms on affected trees resemble deficiencies in water and nutrient supplies, expressed as leaf rolling, chlorosis and early reddening, leading to sudden dieback during the growing season. Small, wilted fruit and dried leaves may also persist during the autumn. Phytoplasmas belonging to the 16SrX‐B subgroup of European stone fruit yellows (ESFY) were identified by nested polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…This group is classified as 16SrX (Apple proliferation group) based on restriction fragment length polymorphism analysis of 16S rDNA sequences (Lee et al, 1995). This group X was further subdivided into subgroups A, B, C, D, E which correspond to the strain designations AP, ESFY, PD, SPAR and BWB respectively (Lee et al, 1995;Davis & Sinclair, 1998;Laimer Da Câmara Machado et al, 2001). Subsequent reports suggest that BWB should be represented as a single phytoplasma group separate from the AP group (Seemüller et al, 1998;Mäurer & Seemüller, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group is classified as 16SrX (Apple proliferation group) based on restriction fragment length polymorphism analysis of 16S rDNA sequences (Lee et al, 1995). This group X was further subdivided into subgroups A, B, C, D, E which correspond to the strain designations AP, ESFY, PD, SPAR and BWB respectively (Lee et al, 1995;Davis & Sinclair, 1998;Laimer Da Câmara Machado et al, 2001). Subsequent reports suggest that BWB should be represented as a single phytoplasma group separate from the AP group (Seemüller et al, 1998;Mäurer & Seemüller, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the phytoplasmas are eliminated in the above ground parts in winter and survive in the roots. Laimer Da Câmara Machado et al (2001) also reported that the appearance of symptoms in a tree may not be a reliable indicator of its phytoplasma status because they also found symptomless trees gave a positive ESFY phytoplasma signal. These reports suggest that it is not altogether surprising that we detected AlloY in a symptomless plant as it may have been in remission but with levels of phytoplasma detectable by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 15 years, the importance of ESFY in Austria has significantly increased (Richter ; Laimer Da Câmara Machado et al. ; Riedle‐Bauer et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…(1994) determined the common aetiology of these diseases and proposed the single name ‘European stone fruit yellows’ (ESFY). Occurrences of ESFY have been reported in Spain (Sanchez Capucino & Forner, 1973), France (Desvignes & Cornaggia, 1982), Italy (Giunchedi et al ., 1978), Slovenia (Brzin et al ., 2001), Greece (Rumbos & Bosalidis, 1985), Romania (Ionica, 1985), Germany (Lederer & Seemüller, 1992), Czech Republic (Navratil et al ., 2001), England (Davies & Adams, 2000) and Austria (Laimer da Camara Machado et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%